La division du travail enseignant et ses effets sur les savoirs enseignés - Marie David (Recherches en Éducation)
In high schools and at university, how do teachers to distribute classes and teachings among themselves? I am interested in an aspect of the division of teaching work, the distribution of services, but also to the results of this division on the definition of contents of learning. The service of high school and university teachers forms the practical framework of their activity and has direct consequences on their work, particularly on the way they prepare and deliver their lessons and therefore on the knowledge they will teach. This text is based on a field survey carried out in a major city in the West of France, in two highs schools and in a university. The courses of two school subjects, economic and social sciences, and physics and chemistry, and three university subjects (physics, chemistry, sociology) were observed during three years